Computerized system and method using image views to find grasp locations and trajectories - CLAUSSEN HEIKO; APARICIO OJEA JUAN L; WEN CHANGTAO; SEHR MARTIN; SOLOWJOW EUGEN (2020)
A computerized system and method are provided. A robotic manipulator (12) is arranged to grasp objects (20). A gripper (16) is attached to robotic manipulator (12), which includes an imaging sensor (14). During motion of robotic manipulator (12), an imaging sensor (14) is arranged to capture images providing different views of objects in the environment of the robotic manipulator. A processor (18)is configured to find, based on the different views, candidate grasp locations and trajectories to perform a grasp of a respective object in the environment of the robotic manipulator. The processor(18) is configured to calculate respective values indicative of grasp quality for the candidate grasp locations, and, based on the calculated respective values indicative of grasp quality for the candidate grasp locations, the processor (18) is configured to select a grasp location likely to result in a successful grasp of the respective object. 本发明提供了计算机化的系统及方法。机器人操纵器(12)布置为抓取对象(20)。抓具(16)附接到该机器人操纵器(12)，其包括成像传感器(14)。在机器人操